Pengaruh Current Ratio (CR) Dan Total Asset Turn Over (TATO) Terhadap Return On Assets (ROA) Pada Sektor Manufaktur Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Via Rahma Yanti; Ninik Dwi Atmini (Universitas Kristen Indonesia Toraja, 2023)
This study aims to determine the effect of Current Ratio (CR) and Total Assets Turnover (TATO) affect the Return On Assets (ROA) of food and baverage Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The independent variables used are Current Ratio (CR) and Total Assets Turnover (TATO). While the dependent variable used is Return On Assets (ROA). This type of research uses quantitative research methodology. The population in this study is food and baverage manufacturing industry companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period, namely 72 companies. For sampling using purposive sampling techniques, 23 food and baverage manufacturing companies were obtained that met the criteria. The amount of data processed by 23 companies times 5 (five) years, so there are 115 data. Data analysis techniques in this study using Multiple Linear Regression analysis. The results of this study show that 1). The Current Ratio partially have a positive and significant impact on Return On Assets. 2). Total Assets Turnover (TATO) partially have a positive and significant impact on Return On Assets.